Method of closed loop springback compensation for incremental sheet forming process - Han, Fei; Mo, Jian-hua; Gong, Pan; Li, Min (Journal of Central South University, 2011)
The closed loop control model was built up for compensating the springback and enhancing the work piece precision. A coupled closed loop algorithm and a finite element method were developed to simulate and correct the springback of incremental sheet forming. A three-dimensional finite element model was established for simulation of springback in incremental sheet forming process. The closed loop algorithm of trajectory profile for the incremental sheet forming based on the wavelet transform combined with fast Fourier transform was constructed. The profile of processing tool path of shallow dishing with spherical surface was designed on the basis of the profile correction algorithm. The result shows that the algorithm can predict an ideal profile of processing track, and the springback error of incremental sheet forming is eliminated effectively. It has good convergence efficiency, and can improve the workpiece dimensional accuracy greatly.